AKSI PEDULI KESEHATAN DAN TRAUMA HEALING BAGI PENGUNGSI GEMPA SULBAR DI KABUPATEN MAJENE - Syarifuddin Yusuf; Haniarti Haniarti; Syaiful Amir; Usman Usman; Reinhard Reinhard; Syafira Maharani S; Nurpika Hardiyanti (Universitas Muhammadiyah Tapanuli Selatan, 2021)
Indonesia's position is very vulnerable to disasters, because it is at the junction of three tectonic plates (Australia, Eurasi and Pacific), so it is called a super market for all types of disasters that exist. The West Sulawesi earthquake had a wide impact on material damage and casualties. Earthquake victims saved themselves in the relatively safer refugee camps. The targets to be achieved are the implementation of health checks and medication, trauma-healing therapy, and providing food and clothing assistance for refugees as well as conducting tertiary tridharma activities through community service. Meanwhile, the output of the activity is published in community service journals indexed by SINTA. Implementation of Action for West Sulawesi Earthquake Fikes Muhammadiyah University Parepare collaboration Lazismu Parepare as many as 15 personnel, with the following stages: 1) Planning; 2) Preparation; and 3) Implementation of the Action; For 3 days in 3 refugee locations in Majene Regency.The results of the medical team's examination and treatment, as many as 115 refugees identified hypertension, gout, cholesterol, ulcers, while itching, coughing, diarrhea were felt while in the evacuation, because they interacted and did not care about the COVID-19 pandemic health protocol. Meanwhile, the trauma healing team provided entertainment therapy, games and games in the form of singing, clapping spirits, gymnastics, balloon dancing competitions, giving rewards, tree hopes and giving gifts to 98 children and distributing 204 packages of food and clothing assistance to refugees